Obraz kobiety w twórczości Anandy Devi - Szkonter-Bochniak, Anna (Śląskie Studia Polonistyczne, 2020)
Ananda Devi, an accomplished modern writer from Mauritius, creates texts that are difficult to classify according to their style and genre. The author is reluctant to accept the treatment of her writings as feminist, particularly Western European feminist, they are surely closer to postcolonial feminism and eco-feminism. Nevertheless, the status of women, their rights and tolerance for otherness are the key elements of Devi’s artistic expression. Her characters rebel against the patriarchal society, they endeavour to discover their own place and identity, which frequently means regaining control over their bodies in the first stage of the transformation. Devi’s female characters live close to nature, where they find comfort, some of them go through a regress to the world of animals and plants.